PENGARUH STRUKTUR MODAL, DIVIDEND PAYOUT RATIO DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN CONSUMER GOODS INDUSTRY DI BURSA EFEK INDONESIA TAHUN 2014-2017 - Oktavia, Carolline; Harianto, Cherry; Ericsson, Ericsson; Suwongso, Melly; Jenny, Jenny (Aksara Public, 2018)
This study aims to investigate the influence of capital structure, dividend payout ratio and investment decisions to company value in consumer goods companies listed on the Indonesia Stock Exchange in 2014-2017. This study uses quantitative research methods. Data collection techniques used are documentation techniques and secondary data collection from the financial statements of the Consumer Goods Industry companies listed on the Indonesia Stock Exchange in 2014-2017. The sample used in this study were 72 consisting of 18 companies with 4 research periods. Method of data analysis used in this study wasmultiplelinear regression techniques with SPSS application. Data testing was done by classical assumption test, coefficient of determination test, F test and t test. Conclusions from the results of this study partially capital structure, dividend payout ratio and investment decisions have a positive and significant effect on company value while simultaneously capital structure, Dividend Payout Ratio and investment decisions jointly influence and significant effect on company value. Where the error rate used is 5 % or 0.05 at significant level of 95%